Novel multistage solid–liquid circulating fluidized bed: liquid phase mixing characteristics. (17th February 2020) - Thombare, Manjusha A.; Kalaga, Dinesh V.; Bankar, Sandip B.; Kulkarni, Rahul K.; Satpute, Satchidanand R.; Chavan, Prakash V.
Abstract: Liquid phase axial mixing studies have been carried out in the novel solid–liquid circulating fluidized bed (SLCFB). The SLCFB primarily consists of a single multistage column (having an inner diameter of 100 mm i.d. and length of 1.40 m) which is divided into two sections wherein both the steps of utilization, namely loading (e.g., adsorption and catalytic reaction) and regeneration of solid phase, can be carried out simultaneously in continuous mode. Weak base anion exchange resin was used as the solid phase, whereas water as the fluidizing medium. The effects of physical properties of solid phase, superficial liquid velocity, and solid circulation rate on liquid phase axial dispersion coefficient were investigated. The dispersion coefficient increases monotonically with an increase in the size of solid particle, superficial liquid velocity, and solid circulation rate. The axial dispersion model (ADM) was used to model experimental residence time distribution (RTD) data. A good agreement was found between ADM predictions and the experimental measurements. A unified correlation has also been proposed to determine dispersion coefficient as a function of physical properties of solid and liquid phases, superficial liquid velocity, and solid circulation rate based on all previous and present experimental data on multistage SLCFB.